Practical approaches to development planning : Korea's second five-year plan - Adelman, Irma. (Baltimore : Johns Hopkins Press, 1969)
This book is about the planning of korea formation in national development strategy for the period of the second five year economic development plan
Based on a conference held in St. Charles, Ill., in June 1968.
Includes index.
Includes bibliographical references: p. 293-300.
oo 28/08/2018
Loans
Keywords: Korea